2009
DOI: 10.3354/meps08288
|View full text |Cite
|
Sign up to set email alerts
|

Role of krill versus bottom-up factors in controlling phytoplankton biomass in the northern Antarctic waters of South Georgia

Abstract: The extent to which Antarctic phytoplankton stocks are controlled by 'bottom-up' and/or 'top-down' factors is highly variable. Here we consider data collected at South Georgia during 3 summer surveys that recorded substantial hydrographic variability. A suite of bottom-up and top-down controlling factors were measured simultaneously at the mesoscale. Sea surface temperature varied by > 2°C, macronutrients ranged from near-winter concentrations to near-depleted, while mean densities of a major grazer, krill Eup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…This is not surprising given the various independent factors that can influence surface Chl a concentrations. Among these: mixed layer depth and its effects on bloom dilution (Smetacek and Naqvi, 2008), dust input (e.g., Gassó et al, 2010), composition of the bloom (diatoms versus flagellates) and grazing (Whitehouse et al, 2009). Variations in flow intensity and pathways of the ACC fronts around South Georgia (Thorpe et al, 2002;Park et al, 2010;Boehme et al, 2008) are also among the most important factors likely influencing the interannual variability of the bloom: circulation around and then downstream of shallow topographic features is believed to control the magnitude of sediment-derived iron input to the water column (i.e., due to re-suspension processes) as well as its transport to more distant regions de Jong et al, 2012;Nishioka et al, 2011;Planquette et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising given the various independent factors that can influence surface Chl a concentrations. Among these: mixed layer depth and its effects on bloom dilution (Smetacek and Naqvi, 2008), dust input (e.g., Gassó et al, 2010), composition of the bloom (diatoms versus flagellates) and grazing (Whitehouse et al, 2009). Variations in flow intensity and pathways of the ACC fronts around South Georgia (Thorpe et al, 2002;Park et al, 2010;Boehme et al, 2008) are also among the most important factors likely influencing the interannual variability of the bloom: circulation around and then downstream of shallow topographic features is believed to control the magnitude of sediment-derived iron input to the water column (i.e., due to re-suspension processes) as well as its transport to more distant regions de Jong et al, 2012;Nishioka et al, 2011;Planquette et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Trivelpiece et al 2011). Furthermore, evidence is increasing that krill fulfil complex roles in ecosystem feedback loops through grazing and nutrient recycling (Tovar-Sanchez et al 2007, Whitehouse et al 2009, Schmidt et al 2012. Because Antarctic krill populations and marine ecosystems are responding to climate change, resource and conservation management in the Southern Ocean will need to become much more adaptive.…”
Section: Introductionmentioning
confidence: 99%
“…Weaker winds reduce mixing processes but also generate a microclimate with greater sunshine and higher local air temperatures (Brandon et al, 1999) that will locally modify the properties and vertical structure of the water column. Moreover, Brandon et al, 1999 andWhitehouse et al, 2009 indicated that the eastern shelf region of the island is rich in biological activity, therefore topdown controls by macrozooplankton like krill, not included in the model (Fig. 3) could also locally control phytoplankton biomass.…”
Section: Atmospheric and Sedimentary Sources Of Ironmentioning
confidence: 99%